Construction of an iron and oxygen co-doped nickel phosphide based on MOF derivatives for highly efficient and long-enduring water splitting. Issue 8 (18th February 2020) - Lin, Can; Wang, Dingqian; Jin, Huihui; Wang, Pengyan; Chen, Ding; Liu, Bingshuai; Mu, Shichun
Abstract : (Fe0.1 Ni0.9 )2 P(O)/NF is one of the excellent water-splitting electrocatalysts among non-precious metal electrocatalysts. Abstract : The exploitation of high catalytic activity electrocatalysts with abundant earth reserves is the prerequisite for extensive hydrogen production from water electrolysis. Herein, based on a feasible design idea, we fabricate an iron and oxygen co-doped nickel phosphide ((Fe0.1 Ni0.9 )2 P(O)) by phosphating metal–organic framework (MOF) derivatives supported on nickel foam (NF) for efficient water splitting. In 1.0 M KOH, the (Fe0.1 Ni0.9 )2 P(O)/NF electrode only requires an overpotential of 240 mV to reach 100 mA cm −2 for the OER and 87 mV to reach 10 mA cm −2 for the HER, respectively. Encouragingly, an alkaline electrolyzer assembled with the (Fe0.1 Ni0.9 )2 P(O)/NF electrode can achieve a current density of 10 mA cm −2 at an extremely low voltage of 1.50 V, which is one of the lowest values currently achievable with non-precious metal electrocatalysts. Undoubtedly, this work provides a novel and practical strategy to synthesize highly efficient and durable electrocatalysts based on MOF derivatives for overall water splitting and other electrocatalysis.